EFEKTIFITAS PLIOMETRIK PUSH UP UNTUK MENINGKATKAN DAYA LEDAK OTOT LENGAN - Ganesa P.D. Kurniawan; Ahmad Syakib (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2022)
Background: Muscular power is a person's ability to use the maximum strength deployed in the shortest possible time. In this case, it is stated that muscle power = strength (force) X speed (velocity). Plyometrics is a practical exercise in increasing explosive muscle power (power). Because in this exercise, the stretch reflex in the muscles is repeated to produce an explosive reaction. The conscious and unconscious movement processes involved in plyometrics are the so-called stretch reflex, also called the spindle reflex or myotatic reflex (spindle reflex or myotatic reflex). The tools or devices for the 4-axis reflex and the stretch reflex are the main components of the overall control of the nervous system for body movement (Radcliffe & Farentinos, 2002). Objective: To determine the effectiveness of plyometric push-up exercises on arm muscle explosive power at the Matador Volleyball Club. Results: The analysis results for the plyometric push-up group got a p-value = 0.000 (<0.05). In contrast, the results for the conventional push-up group got a p-value = 0.000 (<0.05), and based on the results of the difference test, a p-value of 0.000 was obtained. <0.05 Conclusion: There is a difference in the effect between the intervention of the two treatment groups. Plyometric push-up exercises are more effective than conventional push-up exercises in increasing arm muscle explosive power in members of the Matador Volly Ball Team.